The effect of on-the-job training and education level of employees on innovation in emerging markets - Kyunga Na (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study investigates the effects of on-the-job training and education level of employees on innovation in emerging markets using sample firms from BEEPS 2013 (Business Environment and Enterprise Performance Survey 2013) datasets provided by the World Bank. The Heckman two-stage regression model is used in order to control for endogeneity over a final sample of 10,366 firms in Eastern Europe and Central Asia. To estimate innovation of firms, five indicators of innovation (product, process, organizational, marketing innovation, and R&D investments) are considered. The results of the study suggest that both on-the-job training and education level of employees have significant and positive impact on all forms of innovation. This finding implies that firms in Eastern European and Central Asian emerging markets can promote innovation by offering more on-the-job training programs or recruiting more educated employees.
Keywords: 650; innovation; on-the-job training; education level of employees; BEEPS 2013; emerging markets